Disseminating our knowledge in an inclusive society: An inaugural editorial statement - Kananga Robert Mukuna (International Journal of Studies in Inclusive Education)
Inclusive research is essential at all stages of research, including data collection and dissemination. This essay investigates how current literature and the practical application of inclusive practices in the academic setting illuminate this critical but often overlooked aspect of research. It offers the South African policy of Working Paper 6 (WP6) to clarify how the principle and policy of education for all learners can be implemented in inclusive societies and development, which confront various obstacles due to psychosocial issues. It discourses the purpose of the South African Policy of WP6 and its discourses in multiple contexts by adopting innovative and more inclusive techniques for dissemination, intellectual and developmental disability research, and analysis that can reach far beyond the academic walls. It finally discusses barriers to inclusive dissemination and methods to overcome them. Even though further research needs to be explored in this regard, this article would be beneficial to scholars to champion and implement inclusivity to make research more meaningful and accessible to all who are affected by any form of exclusion and discrimination in our society.